Centralidade urbana em cidade de porte médio : análise em Passo Fundo/RS - Gradin, Roberta (2013)
Sustainability in urban medium city can be obtained by structuring the urban space, in other words, by the relative location of the centers and their interrelationships. The urban centralities, formed spontaneously or planned, are characterized by the concentration of activities, land use diversity, availability of urban equipment, facilities and displacement conditions. The study analyzes the centrality in the medium city, checking the contribution to urban sustainability in relation to residents location and perception. A case study was conducted in the city of Passo Fundo, RS, identifying the urban structure in downtown and four major subcenters, Boqueirão, Vera Cruz, Petropolis and São Cristóvão, which centralities are linear along the access roads to the regional road system. In subcenter better structured, São Cristóvão neighborhood ,we´ve made diagnostics of urban structure and residents' satisfaction in relation to equipment, services and activities available, frequency and dislocations way, if restricted to the sub-center or dependent on other centralities. The results indicate that this subcenter exercise a partial centricity, related to neighborhood trade and education equipment. The main center to a greater degree, and other subcenters, exercise strong attraction when refers to health care, culture, leisure, trade and specialized services. As for the dislocations in the neighborhood and to other neighborhoods, there is a predominance of individual transport by car, surpassing dislocations on foot or public transportation. Although the diversification and consolidation of the sub-center on contributing to urban sustainability, several strategies are recommended to encourage land use and activities diversification and the reduction of dislocations, applicable in the qualification of subcentralities in urban medium city